Quantifying Diversity and Composition of Tree Species in Secondary Hill Forests of Chunati Forest, Chittagong, Bangladesh - Mamun, A.; Akhter Hossain, M.; Hossain, M. K.; Alam, S. (Indian Forester, 2015)
Diversity and composition of tree species of secondary Dipterocarp hill forests in Chunati Wildlife Sanctuary of Chittagong was quantified through 37 sample plots of 20 m x 20 m in size taken randomly over the period of December 2012 to June 2013. A total of 993 individual trees having â‰¥5 cm dbh (671 trees ha-1) of 99 species belonging to 73 genera and 36 families were recorded from the forests of Chunati. The forest has diverse floristic resources that seemed from the Shannon Wiener’s diversity index (3.353), Margalef’s richness index (14.201) and Simpson’s dominance index (0.090). Total basal area of tree species was 12.47 m2 ha-1, where Dipterocarpus turbinatus showed highest basal area (2.62 m2 ha-1) followed by Acacia auriculiformis (1.39 m2 ha-1 ). Importance Value Index (IVI) was found maximum (40.11) for Acacia auriculiformis followed by Tectona grandis (16.46) plantation species. On the other hand, importance value Index was highest for Dipterocarpus turbinatus (25.10) followed by Ficus hispida (19.76) for natural species.